Sawmilling safety and accident prevention in Selangor, Malaysia - Jusoff, Kamaruzaman (1989)
A limited interview and questionaire survey was carried out in October 1988 at 10 selected sawmills in the state of Selangor, Malaysia to examine and analyse the status of safety and accident prevention. The nature, trend and causes of accidents in the sawmills were highlighted. The status of accident prevention was also presented. Little attention to occupational safety and accident prevention was given by the sawmill companies. An appraisal on the number of death was attempted. However, the companies were quite reluctant in giving information as to the statistics to monitor fatal accident rates in their companies, except accidents involving minor injuries. There is an immediate and urgent need for further research to improve the working conditions in the Malaysian sawmills, particularly in Selangor as lack of safety measures and accident prevention are costing the sawmilling industry at least a few thousand Malaysian Ringgit annually.